2016
DOI: 10.3758/s13428-016-0810-5
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Lexicon Project: A megastudy of lexical decision performance for 25,000+ traditional Chinese two-character compound words

Abstract: Using a megastudy approach, we developed a database of lexical variables and lexical decision reaction times and accuracy rates for more than 25,000 traditional Chinese twocharacter compound words. Each word was responded to by about 33 native Cantonese speakers in Hong Kong. This resource provides a valuable adjunct to influential mega-databases, such as the Chinese single-character, English, French, and Dutch Lexicon Projects. Three analyses were conducted to illustrate the potential uses of the database. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
131
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(163 citation statements)
references
References 44 publications
(61 reference statements)
7
131
3
Order By: Relevance
“…As in previous megastudies (Ferrand et al, 2010;Keuleers, Diependaele, & Brysbaert, 2010;Tse et al, 2016), we determined the reliability of accuracy and RTs in order to evaluate how useful they might be. For each word, participants were split in two groups each containing half of the participants having seen that word.…”
Section: Reliability Of the Megalex Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous megastudies (Ferrand et al, 2010;Keuleers, Diependaele, & Brysbaert, 2010;Tse et al, 2016), we determined the reliability of accuracy and RTs in order to evaluate how useful they might be. For each word, participants were split in two groups each containing half of the participants having seen that word.…”
Section: Reliability Of the Megalex Measuresmentioning
confidence: 99%
“…As Tse et al (2016, p. 7) put it, "Word frequency has consistently been shown to be one of the strongest predictors of visual word recognition in various languages.…”
Section: Stimulus Durationmentioning
confidence: 99%
“…One of the first data sets of this scale was the English Lexicon Project (Balota et al, 2007), which contains responses from visual lexical decision and naming tasks of North American English. More recently, similar studies have been completed for British English (Keuleers et al, 2012), Dutch , French (Ferrand et al, 2010), and Cantonese (Tse et al, 2016), as well as a database of lexical decision and naming across the lifespan for German (Schröter & Schroeder, 2017). These large-scale studies or "megastudies" (Seidenberg & Waters, Small targeted experiments often suffer from sampling difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Another unique characteristic of Chinese characters is that visually complex characters (i.e., high stroke counts) occupy the same amount of space as non-visually-complex characters (e.g., 墙 vs. 力), thereby allowing researchers to select characters with either a high or low information density. Research has shown that RTs in a lexical decision task increase as the complexity of the characters increases (e.g., Tse & Yap, 2018;Tse et al, 2017). Thus, the purpose of the present study was to gather normative data for Chinese-English pairs, which will be of high interest to those wishing to generalize their research to a logographic language, which has many unique characteristics that could further inform psychological theories.…”
mentioning
confidence: 99%